2017
DOI: 10.1136/bcr-2017-220240
|View full text |Cite
|
Sign up to set email alerts
|

Invading beyond bounds: extraintestinalClostridium difficileinfection leading to pancreatic and liver abscesses

Abstract: has become a common healthcare-associated infection over the past few years and gained more attention. was estimated to cause almost half a million infections in USA in 2011 and 29 000 died within 30 days of the initial diagnosis. Although colitis due to is the most common presentation, there have been reported cases of extraintestinal infections. As per our review of literature, this is the third reported case of liver abscess due to the organism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Extraluminal C. difficile infection is not common, reflecting 0.1% of total C. difficile infections 1,2 . Extraintestinal manifestations include peritoneal infections, osteomyelitis, wound infection, perianal abscess, bacteremia, urinary tract infections, lung infections, and reactive arthritis 1,3–9 . Several cases of secondary bacterial peritonitis due to C. difficile have been previously described in the literature, but only 11 cases of SBP have been reported 1,3,4,10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extraluminal C. difficile infection is not common, reflecting 0.1% of total C. difficile infections 1,2 . Extraintestinal manifestations include peritoneal infections, osteomyelitis, wound infection, perianal abscess, bacteremia, urinary tract infections, lung infections, and reactive arthritis 1,3–9 . Several cases of secondary bacterial peritonitis due to C. difficile have been previously described in the literature, but only 11 cases of SBP have been reported 1,3,4,10 …”
Section: Discussionmentioning
confidence: 99%
“…1,2 Extraintestinal manifestations include peritoneal infections, osteomyelitis, wound infection, perianal abscess, bacteremia, urinary tract infections, lung infections, and reactive arthritis. 1,[3][4][5][6][7][8][9] Several cases of secondary bacterial peritonitis due to C. difficile have been previously described in the literature, but only 11 cases of SBP have been reported. 1,3,4,10 Most reported infections of extracolonic C. difficile have been polymicrobial.…”
Section: Discussionmentioning
confidence: 99%
“…The most common form of symptomatic CDI is enterocolitis followed by pseudomembranous colitis, and less commonly, toxic megacolon [3] . Colitis is the most common manifestation of CDI but there are occasional reported cases of extraintestinal infections (EI) including bacteraemia, pyogenic liver abscess, intraabdominal abscess, and brain abscess [4][5][6] . Overall, the reported frequency of EI CDI is between 0.17% and 0.6% [6] .…”
Section: Discussionmentioning
confidence: 99%
“…It is important to report that most cases of extraintestinal CDI were polymicrobial in nature, Marina et al [26] reported on anaerobic pleuropulmonary infections and found that of 116 organisms isolated, only two were Cd and only one of these was isolated in a pure culture. Roy et al [27] described a patient presented with hepatic and pancreatic abscess with a polymicrobial infection. With the findings of sigmoid perforation, they considered the route of infection being translocation of bacteria across the gastrointestinal lumen due to colonic inflammation with direct seeding to the site.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%